A critical review on keeta visha: an ayurvedic approach - Kumar, Parvesh; Goswami, Ashish B. (Creative Pharma Assent, 2016)
Indian system of medicine plays an important part in health care system all over India. Ayurveda is an ancient Indian system of medicine having eight important branches. Agad tantra is among one of them which deals with toxicological conditions and their management. Sage Susruta in Kalpasthaana of his work Susruta Samhita, and Sage Vaagbhata in Uttaratantra of his work Ashtaanga Hrdaya, and in other classics and regional texts have narrated regarding the origin of Visha and Keeta Visha. There are several types of Keeta Visha described. Among animal poisoning, Acharayas have described different creatures (Sarpa, Keeta, and Luta) responsible for life threatening situations. The importance of Keeta Visha is more because it causes severe manifestations in the human being, even death also. Acharya Suhsruta described Keeta Visha under Jangama Visha and explained 67 varieties of Keeta under 4 groups. According to its variety diagnosis and treatment of Keeta Visha is found to be very difficult because these varieties are not yet correctly identified and besides, regional variations of these Keetas manifests very differently.